INTENSIFICATION OF WATER TREATMENT TECHNOLOGY BY DISCRETE-PULSE ENERGY INPUT - Лимар, Анна; Радченко, Наталія; Іваницький, Георгій; Сидоренко, Віталій; Долінський, Анатолій; Ободович, Олександр; Целень, Богдан (SWorldJournal, 2022)
The application of the method of discrete-pulse energy input for neutralization of the condensate of natural gas combustion products, intensification of aeration treatment of water during purification from iron and manganese ions and reducing the total w